2016
DOI: 10.1101/041327
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

South Asia as a reservoir for the global spread of ciprofloxacin resistantShigella sonnei

Abstract: 59Background 60 Antimicrobial resistance is a major issue in the Shigellae, particularly as a specific multidrug resistant 61 (MDR) lineage of Shigella sonnei (lineage III) is becoming globally dominant. Ciprofloxacin is a 62 recommended treatment for Shigella infections. However, ciprofloxacin resistant S. sonnei are being 63 increasingly isolated in Asia, and sporadically reported on other continents. 64 Methods and Findings 65Hypothesising that Asia is the hub for the recent international spread of ciproflo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…We confirmed that global FQr S. sonnei are clonal and likely emerged in South Asia around early 2007. This finding is in agreement with a wealth of epidemiological data citing the rise of FQr S. sonnei since 2007 9 . It is notable that the second and third mutations ( parC -S80I, gyrA -D87G) were acquired rapidly in the last two decades, coinciding with a sharp increase in the use of FQ during this period, when these drugs became routinely prescribed for shigellosis 6,41 .…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…We confirmed that global FQr S. sonnei are clonal and likely emerged in South Asia around early 2007. This finding is in agreement with a wealth of epidemiological data citing the rise of FQr S. sonnei since 2007 9 . It is notable that the second and third mutations ( parC -S80I, gyrA -D87G) were acquired rapidly in the last two decades, coinciding with a sharp increase in the use of FQ during this period, when these drugs became routinely prescribed for shigellosis 6,41 .…”
Section: Discussionsupporting
confidence: 91%
“…Our previous analysis of 70 representative FQr S. sonnei suggested that they emerged as a single clone (nested within CenAsiaIII) in South Asia and subsequently radiated internationally 9 . Here, we utilised a collection of 411 internationally isolated S. sonnei , including 265 contemporary isolates sequenced for the purpose of this study (Table 1).…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations